2014
DOI: 10.1155/2014/701094
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Selectively Regulatory Roles of IL-23/IL-17 Axis in the Lesions of Oral Lichen Planus

Abstract: Interleukin- (IL-) 23/IL-17 axis is a newly discovered proinflammatory signaling pathway and has been implicated in the pathogenesis of many chronic inflammatory and immune disorders. Here we investigated whether the IL-23/IL-17 axis was present and functional in the lesions of oral lichen planus (OLP), a chronic inflammatory disease affecting the oral mucosa. Using immunohistochemistry and quantitative PCR, we found that the subunits of IL-23 and IL-17 were overexpressed in OLP lesions than in normal oral muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 42 publications
1
86
2
2
Order By: Relevance
“…cells were infrequent overall, but were more common in the NSI tissues than the OLP tissues, and were found deeper in the connective tissue. These findings contrast with the reports from others [13,18], who described more sub-epithelial IL17 ? cells in OLP in comparison with normal mucosal controls.…”
Section: Discussioncontrasting
confidence: 99%
“…cells were infrequent overall, but were more common in the NSI tissues than the OLP tissues, and were found deeper in the connective tissue. These findings contrast with the reports from others [13,18], who described more sub-epithelial IL17 ? cells in OLP in comparison with normal mucosal controls.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, some reports demonstrated that IL-17A played a protective role against bacterial infections by recruitment to mobilization of neutrophils [8]. While in our previous investigations, it demonstrated that expression level of IL-17A may be associated with disease severity in periodontitis [5,6] and may also had potential regulating role to human oral keratinocyte cell lines [9].…”
Section: Introductionmentioning
confidence: 63%
“…Pain, the duration of the disease and spread of the lesions that first appeared on the heel may be the result of constant exposure to trauma due to lesion location in this case. While the etiology of the disease is not fully understood, studies show damage to keratinocytes following an immune reaction caused by CD8+ lymphocytes where production of multiple mediators (interleukin-12, interferon-γ, tumor necrosis factor-α, RANTES, MMP-9 and transforming growth factor-β1) gets suppressed and T-cell mediated immunity gets irregular [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…Erosive lichen planus (ELP) is a rare form of LP usually involving the oral mucosa and genital area 2 . Although the etiology of the disease is not fully understood, autoimmune diseases are thought to be associated with LP [3][4][5] . Psychological and emotional disorders are also thought to have a role 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation